Natural splice variant of MHC class I cytoplasmic tail enhances dendritic cell-induced CD8+ T-cell responses and boosts anti-tumor immunity. - Tania G Rodríguez-Cruz; Shujuan Liu; Jahan S Khalili; Mayra Whittington; Minying Zhang; Willem Overwijk; Gregory Lizée (PLoS ONE)
Dendritic cell (DC)-mediated presentation of MHC class I (MHC-I)/peptide complexes is a crucial first step in the priming of CTL responses, and the cytoplasmic tail of MHC-I plays an important role in modulating this process. Several species express a splice variant of the MHC-I tail that deletes exon 7-encoding amino acids (Δ7), including a conserved serine phosphorylation site. Previously, it has been shown that Δ7 MHC-I molecules demonstrate extended DC surface half-lives, and that mice expressing Δ7-K(b) generate significantly augmented CTL responses to viral challenge. Herein, we show that Δ7-D(b)-expressing DCs stimulated significantly more proliferation and much higher cytokine secretion by melanoma antigen-specific (Pmel-1) T cells. Moreover, in combination with adoptive Pmel-1 T-cell transfer, Δ7-D(b) DCs were superior to WT-D(b) DCs at stimulating anti-tumor responses against established B16 melanoma tumors, significantly extending mouse survival. Human DCs engineered to express Δ7-HLA-A*0201 showed similarly enhanced CTL stimulatory capacity. Further studies demonstrated impaired lateral membrane movement and clustering of human Δ7-MHC-I/peptide complexes, resulting in significantly increased bioavailability of MHC-I/peptide complexes for specific CD8+ T cells. Collectively, these data suggest that targeting exon 7-encoded MHC-I cytoplasmic determinants in DC vaccines has the potential to increase CD8+ T-cell stimulatory capacity and substantially improve their clinical efficacy.